Congenital Heart Disease Fetuses Have Decreased Mid-Gestational Placental Flow, Placental Malperfusion Defects, and Impaired Growth - Rebecca Josowitz, MD, PhD; Deborah Y. Ho, MD, MPH; Somya Shankar, BS; Antara Mondal, MS; Alexis Zavez, PhD; Rebecca L. Linn, MD; Zhiyun Tian, MD; J. William Gaynor, MD; Jack Rychik, MD (JACC: Advances)
Background: Placental health may impact the development and outcomes of congenital heart disease (CHD). CHD fetuses have been shown retrospectively to have decreased placental blood flow. Objectives: The purpose of this study was to determine if CHD fetuses with decreased placental blood flow have placental pathology at birth and if there is a relationship between placental blood flow, placental pathology, and outcomes. Methods: We performed a prospective case-control study of 38 CHD fetuses, including 28 with single ventricle physiology and 36 controls. Demographic, clinical, and postnatal biometric data were collected. Umbilical venous volume flow (UVVF) was measured from 2nd trimester fetal echocardiograms. Placentas underwent standardized pathological analysis. Standard descriptive statistics and regression analyses were performed to analyze the relationship between UVVF, placental defects, and outcomes. Results: CHD fetuses had a 15% decrease in mid-gestational UVVF indexed to fetal weight (P < 0.01), and a 27% reduction in UVVF as a proportion of fetal cardiac output (P < 0.01) compared to controls. CHD fetuses had increased placental maternal vascular malperfusion (MVM) lesions (44% vs 18%, P < 0.05), especially high-grade MVM (39% vs 9.1%, P = 0.05), and a trend toward increased placental fetal vascular malperfusion lesions (42% vs 23%, P = 0.10). Placental MVM but not fetal vascular malperfusion lesions were associated with decreased birth weight in CHD fetuses (P < 0.001). There was no association between UVVF and placental pathologic findings or fetal growth. Conclusions: CHD (particularly single ventricle) fetuses have decreased mid-gestational placental blood flow, increased placental malperfusion defects, and impaired fetal growth. Placental MVM may influence impaired fetal growth in CHD.